2016
DOI: 10.1371/journal.pone.0166992
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Smoking Cessation Medications: A National Prospective Cohort From Taiwan

Abstract: Background and objectiveRelative effectiveness of smoking cessation medications—varenicline, bupropion and nicotine replacement therapy (NRT)—remains unclear among smokers in real-world settings. Evidence in females and smokers with light/moderate nicotine dependence is particularly insufficient. This study compared the effectiveness of varenicline, bupropion or NRT gum relative to NRT patch, in achieving abstinence among recent quitters.MethodsIn a national smoking cessation program in Taiwan (2012–2015), a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…It is well known that a high level of nicotine dependency is a factor that can impinge on the success of smoking cessation efforts [ 22 ], and this study confirmed these results in patients with chronic diseases. Previous Korean and Taiwanese studies have also verified these results [ 10 , 23 ]. Completion of the program was significantly associated with smoking cessation, consistent with the results of our previous study [ 10 ].…”
Section: Discussionsupporting
confidence: 75%
“…It is well known that a high level of nicotine dependency is a factor that can impinge on the success of smoking cessation efforts [ 22 ], and this study confirmed these results in patients with chronic diseases. Previous Korean and Taiwanese studies have also verified these results [ 10 , 23 ]. Completion of the program was significantly associated with smoking cessation, consistent with the results of our previous study [ 10 ].…”
Section: Discussionsupporting
confidence: 75%
“…Nicotine replacement therapy such as patch or gum bupropion as well as counseling are advised in smoking cessation even though the success rate are still unsatisfactory (Karpinski, Timpe, & Lubsch, 2010;Wu et al, 2007). In Taiwan, despite varenicline user reported higher abstinence rate than NRT patch users, the serious neuropsychiatric symptoms observed in adult patients may limit scope of application (Chang, Lo, Chang, Hsueh, & Tsai, 2016). The study showed AA in combination with group counseling is a safe intervention which can lower nicotine reliance and daily tobacco consumption for smoking cessation.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24] The proportion of smokers who wished to quit smoking in Japan was higher among females than males, 2 whereas studies in other countries reported no sex differences. 25,26 Other studies reported no significant sex differences in the maintenance of smoking cessation, [27][28][29] whereas others suggested female varenicline users were more likely to maintain cessation 1 year after quitting. 30 Of note, our results suggest unique sex differences within the Japanese population.…”
Section: Discussionmentioning
confidence: 99%